Comprehensive comparison of various machine learning algorithms for short-term ozone concentration prediction - Yafouz A.; AlDahoul N.; Birima A.H.; Ahmed A.N.; Sherif M.; Sefelnasr A.; Allawi M.F.; Elshafie A. (Elsevier B.V., 2023)
Forecasting; Learning algorithms; Machine learning; Monitoring; Neural networks; Ozone; Public health; Regression analysis; Air quality monitoring; Artificial neural network modeling; Gaussian process regression; Hyper-parameter; Hyper-parameter optimizations; Machine learning models; Ozone concentration; Ozone concentrations predictions; Quality monitoring system; Support vector regressions; Air quality